2013
DOI: 10.1289/ehp.1205350
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Paraben Concentrations and Ovarian Aging among Women from a Fertility Center

Abstract: Background: Parabens are preservatives commonly used in personal care products, pharmaceuticals, and foods. There is documented widespread human exposure to parabens, and some experimental data suggest that they act as estrogenic endocrine disruptors. As far as we are aware, no epidemiologic studies have assessed female reproductive health effects in relation to paraben exposure.Objective: We examined the association of urinary paraben concentrations with markers of ovarian reserve in a prospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 36 publications
6
62
2
8
Order By: Relevance
“…Based on earlier data from women in the same cohort as the current analysis, we reported that PP was associated with diminished ovarian reserve (i.e., antral follicle count) (20). Nevertheless, male paraben concentrations were not associated with fertilization or live birth among their female partners undergoing IVF or IUI treatment (21).…”
Section: Introductionmentioning
confidence: 68%
“…Based on earlier data from women in the same cohort as the current analysis, we reported that PP was associated with diminished ovarian reserve (i.e., antral follicle count) (20). Nevertheless, male paraben concentrations were not associated with fertilization or live birth among their female partners undergoing IVF or IUI treatment (21).…”
Section: Introductionmentioning
confidence: 68%
“…Furthermore, parabens have been detected in breast tumor tissue, and may be associated with the formation of these cancers (Darbre and Harvey, 2008;Kuş et al, 2013). Recent studies on a series of parabens, including methyl-(MPB), ethyl-(EPB), propyl-(PPB), and butyl-parabens (BPB) (structures are shown in Fig 1) (Karpuzoglu et al, 2013), have revealed that parabens affect estrogen levels, potentially impacting female reproductive health (Smith et al, 2013). Due to their potential toxicity to aquatic organisms and human beings, it is important to study the transformation and removal of these pollutants from water environments.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Studies have also shown detectable levels in pregnant women through urine evaluation, 15,17 but did not evaluate fetal levels. Regarding any potential concern for the developing fetus and newborn postdelivery, it is necessary to first determine whether these substances cross the placenta.…”
Section: Introductionmentioning
confidence: 99%